2020
DOI: 10.1177/1073110520979422
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Firearm Injury through Policy and Law: The Social Ecological Model

Abstract: Rates of firearm injury and mortality are far higher in the United States compared to other high-income nations. Patterns of firearm injury have complex causal pathways; different social contexts may be differentially affected by firearm legislation. In the context of the diversity of social, political, and legal approaches at the state level, we suggest the application of the social ecologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The social–ecological model (SEM) is a conceptual framework for organizing factors that affect health outcomes at the individual, relationship, community, and societal levels (The Social-Ecological and Model 2022 ). The SEM has previously been applied to firearm injury prevention (Durkin et al 2020 ), but not specifically in the pediatric population. Figure 1 presents perceived determinants of firearm safety with respect to children identified in the study organized in accordance with the social–ecological model.…”
Section: Resultsmentioning
confidence: 99%
“…The social–ecological model (SEM) is a conceptual framework for organizing factors that affect health outcomes at the individual, relationship, community, and societal levels (The Social-Ecological and Model 2022 ). The SEM has previously been applied to firearm injury prevention (Durkin et al 2020 ), but not specifically in the pediatric population. Figure 1 presents perceived determinants of firearm safety with respect to children identified in the study organized in accordance with the social–ecological model.…”
Section: Resultsmentioning
confidence: 99%
“…Firearms represent the leading mechanism for homicides and suicides in the United States, causing 75% of homicides and 51% of suicides (CDC, 2020). Like many public health problems, firearm injury is multifactorial with influences and opportunities for prevention at the personal, interpersonal, community, and policy level reflected by the Social-ecological model (Durkin et al, 2020). Our understanding of the risk for firearm injury comes mostly from epidemiologic surveillance data and retrospective studies, but much remains poorly understood, in part because there is little self-reported data from victims themselves and because firearm violence is one of the most understudied public safety, public health, and medical problems in the United States (Stark & Shah, 2017).…”
Section: Introductionmentioning
confidence: 99%